Aversive tension in female adolescents with Anorexia Nervosa: a controlled ecological momentary assessment using smartphones - Kolar, David R. (BMC Psychiatry, 2016)
BACKGROUND: Current models of Anorexia Nervosa (AN) emphasize the role of emotion regulation. Aversive tension, described as a state of intense arousal and negative valence, is considered to be a link between emotional events and disordered eating. Recent research focused only on adult patients, and mainly general emotion regulation traits were studied. However, the momentary occurrence of aversive tension, particularly in adolescents with AN, has not been previously studied. METHOD: 20 female adolescents with AN in outpatient treatment and 20 healthy adolescents aged 12 to 19 years participated in an ecological momentary assessment using their smartphones. Current states of aversive tension and events were assessed hourly for two consecutive weekdays. Mean and maximum values of aversive tension were compared. Multilevel analyses were computed to test the influence of time and reported events on aversive tension. The effect of reported events on subsequent changes of aversive tension in patients with AN were additionally tested in a multilevel model. RESULTS: AN patients showed higher mean and maximum levels of aversive tension. In a multilevel model, reported food intake was associated with higher levels of aversive tension in the AN group, whereas reported school or sport-related events were not linked to specific states of aversive tension. After food intake, subsequent increases of aversive tension were diminished and decreases of aversive tension were induced in adolescents with AN. CONCLUSIONS: Aversive tension may play a substantial role in the psychopathology of AN, particular in relation with food intake. Therefore, treatment should consider aversive tension as a possible intervening variable during refeeding. Our findings encourage further research on aversive tension and its link to disordered eating. TRIAL REGISTRATION: German register of clinical trials (DRKS): DRKS00005228 (Date of registration: September 2, 2013).